PENGARUH STRATEGI PEMBELAJARAN BERBASIS LAGU PERJUANGAN (STRATEGI MENGEKSPRESIKAN SEMANGAT REVOLUSI) TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMPN 1 KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Wati, Helma; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low motivation to learn PPKn student at SMPN 1 Kuantan Mudik. This study aims to determine the effect of learning strategies based on struggle songs (strategies to express the spirit of revolution) on the learning motivation of students in class VIII of SMPN 1 Kuantan Mudik, Kuantan Singingi Regency. This research method is quantitative descriptive, with research instruments in the form of observation sheets, questionnaires and documentation. The statistical analysis used is calculating the average of each class, homogeneity test, Student's T-test distribution, normalized N-Gain test. In the homogeneity test results between classes VIII.3, VIII.4, and VIII5 the three pairs of classes are homogeneous, to determine which class is used as a research sample, then draws as well as between class pairs drawn then draw back to determine the control class and the experimental class , the results are class VIII.3 as the experimental class and class VIII.5 as the control class. Based on statistical analysis, it was obtained Thitung> Ttabel, which is 9.38> 2.016, which means that the struggle-based learning strategy had a positive effect on the learning motivation of students in class VIII of SMPN 1 Kuantan Mudik. Based on this research hypothesis that "struggle song-based learning strategies (strategies to express the spirit of revolution) influence the learning motivation of students in class VIII of SMPN 1 Kuantan Mudik" can be accepted. Based on the N-Gain test with the N-gain of the experimental class 0.5 and the control class 0.03, it can be concluded that the category of development of increased motivation to learn the experimental class is in the medium category and the control class is in the low category.Key Words: Learning Strategy, Song of Struggle, Learning Motivation